Amine-responsive cellulose-based ratiometric fluorescent materials for real-time and visual detection of shrimp and crab freshness - Ruonan Jia (Nature Portfolio, 2019)
Simple, fast, and accurate detection of food freshness has great significance to food safety and business. Here, the authors develop cellulose-based ratiometric fluorescent materials with superior amine-response, which can be used for visual monitoring the freshness of shrimp and crab.